MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN MENYELESAIKAN MASALAH BAHASA INGGRIS DENGAN PEMBELAJARAN KONTEKSTUAL HANDS-ON ACTIVITIES - Maharani Putri; Ance Jusmaya; Okma Permata (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to observe and provide an overview of whether the implementation of Hands-On Activities within a contextual learning framework can enhance students' learning motivation, problem-solving skills, and academic outcomes in English subjects. The research was conducted with students of the Accounting Study Program, Class of 2024/2025, at Universitas Sumatera Barat. The method employed was Classroom Action Research (CAR), consisting of two cycles. The results indicate that students perceive contextual learning through Hands-On Activities as an effective way to increase their learning motivation and problem-solving abilities in English. Furthermore, the findings show that this approach improves students' thinking skills under the guidance of the instructor.Keywords: Learning Activity, Motivation, Handout, English, Students